Becoming a smart solution provider: Reconfiguring a product manufacturer's strategic capabilities and processes to facilitate business model innovation. (December 2022) - Huikkola, Tuomas; Kohtamäki, Marko; Ylimäki, Juho
Abstract: The present study analyzes how a product manufacturer alters its strategic capabilities to become a smart solution provider by employing its dynamic capabilities. We scrutinize how a manufacturer facilitates strategic change by realigning its strategic capabilities and processes from a focus on technical product-development capabilities to product-service-software development capabilities, reconfiguring organizational routines focused on efficiency to routines focused on customer productivity, and shifting from a product logic to a service logic. By studying six leading manufacturing firms based on 86 manager interviews, the present study finds that strategic capabilities are renewed through dynamic capabilities, which involve a reconfiguration of strategic capabilities and processes. Furthermore, manufacturers need to consider the dynamic interplay between resource realignment modes (building digital capabilities, leveraging existing capabilities, accessing external capabilities, and releasing decaying capabilities), hence stressing their reinforcing mechanism to converge products, services, and software. For managers, our study highlights several strategic renewal practices designed to assist and benchmark how strategic capabilities are altered. Highlights: This study scrutinizes how traditional product manufacturers alter their strategic capabilities to become smart solution providers by employing their dynamic capabilities. Manufacturers need to consider the dynamic interplay between resource realignment modes, hence stressing their reinforcing mechanism to converge products, services, and software successfully. The study provides practices for managers to benchmark how capabilities are managed when product manufacturer is becoming a smart solution provider.